Weryfikacja warunków realizacji polskiej polityki naukowej i badawczo-rozwojowej - Szostak, Ewa (The Verification of the Achievement Preconditions of Polish Science and R&D Politics, 2007)
It is well-known, that one of the main factors of competitiveness increase are the actions and processes which influence R&D area and the level of innovativeness of economy. These actions concern directly creation and implementing new technologies and leading in new or improved products. Previous actions concerning increase of competitiveness of economy and realization the assumption of the Lisbon Strategy seem to have no reflection in data describing the state of economy. However, as it is noted above, since 2005 there have been some positive symptoms of changes. The Elaboration of Country Development Strategy 2007-2015 may appear more motivating and better coordinating actions for increasing social and economic cohesion.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 182-192